2014
DOI: 10.1038/nmeth.3025
|View full text |Cite
|
Sign up to set email alerts
|

Spatial control of membrane receptor function using ligand nanocalipers

Abstract: The spatial organization of membrane-bound ligands is thought to regulate receptor-mediated signaling. However, direct regulation of receptor function by nanoscale distribution of ligands has not yet been demonstrated, to our knowledge. We developed rationally designed DNA origami nanostructures modified with ligands at well-defined positions. Using these 'nanocalipers' to present ephrin ligands, we showed that the nanoscale spacing of ephrin-A5 directs the levels of EphA2 receptor activation in human breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
266
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 235 publications
(274 citation statements)
references
References 36 publications
8
266
0
Order By: Relevance
“…Essentially, they noticed that the delivery of siRNAs strongly depends on the density and the spatial orientation of the cancer-targeting ligands of the nanoparticle. Similarly, it has been observed that the membrane receptor-mediated signaling in cancer cells can be regulated by adjusting the spatial orientation of the membrane-binding ligands with DNA origami "nanocalipers" [38]. These observations elegantly show the potential of DNA-based delivery systems, since the vehicle can be easily programmed and functionalized in a user-defined way.…”
Section: Towards Dna-based Drug Delivery Vehicles and Advanced Therapmentioning
confidence: 86%
“…Essentially, they noticed that the delivery of siRNAs strongly depends on the density and the spatial orientation of the cancer-targeting ligands of the nanoparticle. Similarly, it has been observed that the membrane receptor-mediated signaling in cancer cells can be regulated by adjusting the spatial orientation of the membrane-binding ligands with DNA origami "nanocalipers" [38]. These observations elegantly show the potential of DNA-based delivery systems, since the vehicle can be easily programmed and functionalized in a user-defined way.…”
Section: Towards Dna-based Drug Delivery Vehicles and Advanced Therapmentioning
confidence: 86%
“…Hence, the ectodomain of ephrin-B2, normally an integral membrane protein ligand, was conjugated to a soluble biopolymer (hyaluronic acid) to yield multivalent nanoscale conjugates that induced signaling in neural stem cells and promoted their neuronal differentiation in vitro and in vivo. In another nanotechnological twist on the same topic, Shaw et al (12) designed DNA origami nanostructures modified with ligands at well-defined positions and showed that the nanoscale spacing of ephrin-A5 controls membrane receptor activation in breast cancer cells and regulates their invasive behavior. Thus, it is clear that cells are not unacquainted with "nano"; in fact, cells in our body are capable of 'sensing' and responding to nanostructured surfaces.…”
Section: The Right Size In Nanotoxicologymentioning
confidence: 99%
“…[12] Fluorophores have been added to study energy transfer [13] and to create nanoscale barcodes. [14] DNAo rigami structures have also been used to control the shape of metal particles [15] and graphene sheets.…”
mentioning
confidence: 99%